#TITLE_ALTERNATIVE# - Hakim K. (NIM 123 02 030) , Nurwan
Abstract : Simulation of seismic wave propagation is used for modeled or reconstruct seismic wave propagation in a certain geologic model. By solving wave equation using a numerical method one can simulate seismic wave propagation. Solution of the wave equation in a certain time are known as snapshot. Besides a snapshot, one can get a synthetics seismogram as a by product from seismic wave modeling. Using the snapshot of seismic wave propagation and synthetics seismogram we can know how the seismic wave travel and understand seismic events in a certain geologic model. Geologic model that is used for this research is a fault and fold model which is using an acoustic and elastic isotropic assumption. On an acoustic isotropic medium we can modeled P wave through certain model. On an elastic isotropic we can model not only P wave but also S converted wave. From fault and fold model we can see seismic events such as reflection waves, transmission wave etc. Besides a seismic wave events, a wave phenomenon such as bow tie can occur. In this research the reconstruction of a fault model also has been done by create a Brute Stack seismic section. Brute stack seismic section is made by doing a standard seismic data processing on the synthetics seismograms from the results of a simulation seismic wave. From the results of the reconstruction on a fault plane, a reflection seismic events can be seen on Brute Stack section which is describe a geometry of fault model very clear.